PELATIHAN STRATEGI KOMUNIKASI PANTI SOSIAL REHABILITASI WANITA TUNA SOSIAL DALAM MENINGKATKAN CITRA PANTI DI OGAN ILIR - Santoso, Budi; Sakdiyah, Sakdiyah (Lembaga Penelitian dan Pengabdian Masyarakat STISIPOL Candradimuka Palembang, 2020)
Facing problems related to prostituted women (WTS) and women with social problems, the South Sumatra Provincial Social Service established a Technical Implementation Unit (UPT) of the South Sumatra Province Social Service. The image of this rehabilitation center requires a mature communication strategy for UPTD PRWTS managers to socialize the role of PRWTS to the community, especially for those who have the potential to become sponsors in the development of activities at PRWTS. Not only that, the image of the alumni of the social institution is expected to emerge as a positive image from being prostitutes and the result of other social problems to being a person who has a good image and is obedient after undergoing rehabilitation at PRWTS. Ilir. The method or approach used is a qualitative method. The focus of this research is on communication skills training at the Social Rehabilitation Center for Women with Disabilities in Indralaya, Ogan Ilir Regency. The purpose of the Social Rehabilitation Institution for Women with Social Disabilities, Indralaya itself is that women with social problems can be served, educated, and changed their thinking patterns so that these women have a sense of self-esteem, self-confidence, through training in communication skills as well as developing communication strategies to strengthen the image of the orphanage and orphanage alumni to face social life.